The analysis of immunogenic cell death induced by ablation at different temperatures in hepatocellular carcinoma cells - Wang, Mengdong; Duan, Yaxin; Yang, Mao; Guo, Yongfei; Li, Fengtan; Wang, Junping; Si, Tongguo (Frontiers in Cell and Developmental Biology, 2023)
Backgrounds and aims: In the management of hepatocellular carcinoma (HCC), a very deadly malignancy, ablation therapy is a commonly used tool. Its instant result is the outright death of cancer cells. But in the long term, dying cancer cells release a variety of substances that trigger subsequent immune responses. Immunogenic cell death (ICD) has been a trending topic in recent years and has been discussed many times along with oncologic chemotherapy. However, the subject of ablative therapy and ICDs has been little discussed. The purpose of this study was to investigate whether ablation treatment induces ICD in HCC cells and whether different types of ICDs arise as a result of different ablation temperatures. Methods: Four different HCC cells were treated under different temperatures and apoptosis was detected by flow cytometry assay, and a few ICD-related cytokines (calreticulin, ATP, high mobility group box 1, and CXCL10) were detected by immunofluorescence or enzyme-linked immunosorbent assay. Results: The levels of apoptosis and the expression levels of ICD-related cytokines were mostly significantly different between the different groups. Conclusions: Different ablative treatments could induce different types of ICDs in HCC cells, providing a promising track for the development of individualized cancer therapies.